A qualitative study of parents' experiences using family support services: applying the concept of surface and depth. (6th March 2014) - Whittaker, Karen A.; Cox, Pat; Thomas, Nigel; Cocker, Karen
Abstract United Kingdom policy and practice endorses family support for child well‐being. Achieving such support requires multi‐agency approaches that consider all aspects of parents' and children's lives and which offer practical, social and emotional help. The potential for services to make a positive impact on parents and their families will depend in part on the level and nature of engagement. In this paper, a case is made for the application of the two‐part surface and depth concept for understanding how practitioners engage with families and how they might improve the chances of supporting sustainable differences for parents and families. To illustrate, qualitative data from a review of family centre support provided by a north of England local authority are presented. The review was commissioned to explore why families often need to re‐engage with intensive support services. Data were drawn from interviews with parents (n = 18, recruited following a survey of all those registered with the service during April–May 2009) and discussions with family centre support workers (n = 4), and following thematic analysis, three dominant themes emerged – resources available, staff approach and real life – which were appraised in the light of the surface and depth concept. Much of the work with parents effectively dealt with pressing needs. This felt gratifying for both parent and worker and supported immediate service engagement. However, each noted that the more complex issues in parents' lives went unchallenged and thus the sustainability of progress in terms of parenting practice was questionable. A strengths focused approach by staff that understood needs in the context of parents' real‐life circumstances was important to parent engagement. Thus, longer term benefits from family support require practitioners to work with parents to problem solve immediate issues while also digging deeper to acknowledge and seek to resolve the more complex challenges parents face in their real lives.